Properties of playing and tactical thinking of female handball players with different qualification - Frolova, L. S.; Glazirin, I. D.; Petrenko, Y. O.; Kharchenko, I. A.; Timofeev, A. A.; Goncharenko, A. N.; Garyachuk, O.V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
Basic properties of varieties of tactical thought of handballers are considered. The level of their display is shown for the sportswomen of different qualification. 78 sportswomen took part in research. For determination of parameters of tactical and playing thought the method of «Balltest» is utillized in an attack and defence. Priority of exactness and speed of thought is set depending on the level of sporting trade of handballers. Different influence of speed of thought is well-proven on the rightness of decision of playing situations of different orientation in the handballers of mass digits and high level of display of the indicated properties of thought for the sportswomen of high qualification. It is discovered that a level of display of basic properties of tactical thought is in defence substantially below of other varieties of thought. It is marked that with the increase of trade of players there were possibilities to growth of quantitative and speed parameters of tactical thought.